Inability of normal human intestinal macrophages to form multinucleated giant cells in response to cytokines. Issue 6 (December 1995) - Fais, S; Pallone, F
Abstract : Multinucleated giant cells are an important feature of the granulomatous reaction in Crohn's disease (CD) but their cellular origin is poorly understood. The aim of this study was to discover if intestinal macrophages are capable of generating multinucleated giant cells in vitro in response to cytokine stimulation. Human intestinal macrophages were isolated from the intestinal mucosa of CD and uninflamed surgical specimens. Isolated macrophages were cultured in chamber slides with and without exposure to a panel of cytokines and cell activators. Cell fusion, multinucleated giant cells formation, and the expression of adhesion molecules were assessed at various time intervals. In contrast with the autologous peripheral monocytes cell fusion was very poor in cultures of control intestinal macrophages and virtually no multinucleated giant cells were seen. Control intestinal macrophages seemed to poorly express the adhesion molecules required for cell to cell adhesion and fusion, namely ICAM-1 and LFA-1. None of these functions was affected by the exposure to cytokines, including interferon gamma. In cultures of macrophages isolated from CD tissues multinucleated giant cell formation spontaneously occurred as early as three days and was not enhanced by the addition of cytokines. CD macrophages seemed to highly express both ICAM-1 and LFA-1. These data show that human intestinal macrophages are unable to form multinucleated giant cells in response to stimuli and support the concept that they are downregulated in a number of functions. The data also suggest that macrophages participating in the ganulomatous reaction in CD are recruited from the circulation.